Modelos para configuração de rede logística do Programa 'Computadores para Inclusão' - Oliveira, Maritha Gomes Silva de (2014)
The purpose of this work is to study the configuration of the reverse logistical chain post consumption of the computer equipments from the project called "Computadores para a Inclusão" from the Federal Government (MINISTÉRIO DAS COMUNICAÇÕES, 2012). The motivations for the development of this study are the logistical challenges inherent to the disposal of solid human residues, which involve the compromising of society, government and private companies. Particularly, in the case of the electronic equipments, besides the legal aspects foreseen in the Política Nacional de Resíduos Sólidos (PNRS) the opportunities of value recovery for the products are relevant and may increase it´s life cycle. The computer equipments, for example, may be recovered at the Centro de Recondicionamento de Computadores (CRC) which are located where the computers are reconditioned and then made available for needy communities to use. The CRCs belong to the Computers for Inclusion project. One of the difficulties in planning this project is configuring the logistics network, which consists of: (i)defining the computers discharge points; (ii) locating the reconditioning centers, considering the existing places and the possibility of expanding; (iii) in determining the amount of computers present in Telecentros respecting the maximum and minimum number of computers; and (iv) defining the material flow amongst the discharge points, CRCs, Telecentros and the final destination points. In this context, the approach of this study is to propose a mathematical model to help the configuration of the logistical network of the Computadores para a Inclusão" project, contributing to the gathering and appropriate destination of the computer equipments post consumption in all national territory.